Oxford Primary Dictionary - Edited by Allen, Robert [et al.] (Oxford Oxford University Press, 2011)
The best-selling Oxford Primary Dictionary now contains over 40 striking and informative illustrations in a bold new contemporary design. With comprehensive vocabulary coverage, example sentences, and Top Tips giving extra language support this dictionary will take children to the top of Primary school, and enrich their language and spelling.
Keywords: English Language